PRINCESS AND WARRIOR: A COMPARATIVE STUDY OF SNOW WHITE’S CHARACTERIZATION IN SNOW WHITE AND THE SEVEN DWARFS STORYBOOK WITH SNOW WHITE AND THE HUNTSMAN FILM - Arzeti Zunaidi; Chintya Tuffahati Fadhilah; Elaine Atha Zafirah Gumay (E-Journal of Cultural Studies, 2024)
This comparative study investigates on how Snow White has been portrayed in various media. It draws comparisons between the 2012 film Snow White and The Huntsman and the traditional fairy tale Snow White and the Seven Dwarfs, focusing on how her strength and agency are depicted. Snow White is portrayed in classic storybooks as a helpless, innocent character who needs other people's protection. This version of the narrative is frequently based on the Brothers Grimm version (MA Arthawati, 2023). On the other hand, the film presents a rebellious reworking. Snow White shows herself to be a proactive heroine who determines her own course in life. The analysis looks at this change and emphasizes how Snow White is portrayed in the movie as a valiant warrior who is actively against evil, which subverts conventional gender stereotypes (Riris, 2023). Through examining these contrasting portrayals, the study sheds light on the evolving cultural expectations surrounding female characters in fairy tales and their modern adaptations. It reveals how Snow White's characterization reflects a shift towards more empowered and active heroines, resonating with contemporary audiences who seek narratives that challenge traditional tropes of femininity. Throughout looking at these diverse portrayals, the research shows how cultural expectations about female characters in fairy tales and their modern versions have changed over time. As a result, it resonates with modern audiences who are looking for stories that subvert conventional notions of femininity. Snow White's portrayal, it turns out, represents a shift towards more powerful and active heroines. Keywords: Characterization, Cultural and Society, Fairy Tale, Film, Snow White